2012
DOI: 10.1155/2012/576519
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical Instillation of Mitomycin C: A Cause of Delayed Bladder Perforation?

Abstract: We present a case of bladder perforation secondary to intravesical instillation of mitomycin C following transurethral resection of bladder tumour (TURBT) and the role of early detection leading to successful conservative management. We also review the key relevant literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Penna et al 3 reported a 77-year-old Caucasian male who received an early MMC instillation after TURBT. This patient complained of urinary retention after the removal of an indwelling catheter.…”
Section: Discussionmentioning
confidence: 99%
“…Penna et al 3 reported a 77-year-old Caucasian male who received an early MMC instillation after TURBT. This patient complained of urinary retention after the removal of an indwelling catheter.…”
Section: Discussionmentioning
confidence: 99%
“…4 On the other hand, reporting major complications such as bladder perforation, perirectal abscesses, eosinophilic cystitis, and ureteral stenosis is limited to case reports. [5][6][7][8][9][10][11][12][13][14] In this case, we described our experience with bladder perforation after immediate intravesical instillation of doxorubicin.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, reporting major complications such as bladder perforation, perirectal abscesses, eosinophilic cystitis, and ureteral stenosis is limited to case reports. 5 - 14 …”
Section: Discussionmentioning
confidence: 99%